Is Numenius’ Doctrine of the World Souls Identical with Calcidius’ Relevant Doctrine? - Leontitsi, Aikaterini (Conatus - Journal of Philosophy, 2024)
The present article deals with the subject of the doctrine of the Middle Platonist philosopher Numenius about the world souls, according to the testimony of Calcidius. At first, it is being investigated whether the theory presented by Calcidius is an exact reproduction of Numenius’ view or whether some elements have intruded into it, which reveal Calcidius’ view of the soul. Subsequently, the interpretations of the divisible and the indivisible essences of Timaeus – from which the world soul is created – which have been given by Calcidius, Proclus and Numenius are compared. In addition, it is examined whether the source of Calcidius’ interpretation of Timaeus’ psychogony is Numenius or Plotinus. At the same time, the world souls are outlined more clearly according to the theory of Numenius. Finally, what was analyzed above is summarized and some conclusions are drawn, regarding the relationship between the views of Calcidius, Numenius and Plotinus on the universal and human soul, as well as the general character of the system of the last two philosophers.